The impact of integrating technology into students’ presentations on peer evaluation in higher education - Abu-Ayyash, Emad A. S. (2019)
This study investigated the impact of technology in presentations on students’ perception of quality. Students peer reviewed presentations and two external raters evaluated the presentations based on a rubric adapted from Savory (2009). Students reviewed activity using two assessment instruments: a seven point attitudinal scale and a 1–5 ranking scale. The study utilized a mixed methods, embedded QUAN:qual design, where statistical analysis of Pearson Correlation coefficient was paired with qualitative description to discuss the data gathered. The findings showed that students’ scores on the attitudinal scale and their holistic rankings correlated positively with the degree of technology employed in the presentations. The greater the integration of technology in a presentation, the higher the peer rating. However, the external raters’ evalua tions did not generally accord with the student-raters’.